2020
DOI: 10.1128/mbio.03171-19
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Exploits Mitochondrial Contact Site and Cristae Organizing System Complex Subunit Mic10 To Promote Mitochondrial Fragmentation and Cellular Infection

Abstract: Mitochondrial function adapts to cellular demands and is affected by the ability of the organelle to undergo fusion and fission in response to physiological and nonphysiological cues. We previously showed that infection with the human bacterial pathogen Listeria monocytogenes elicits transient mitochondrial fission and a drop in mitochondrion-dependent energy production through a mechanism requiring the bacterial pore-forming toxin listeriolysin O (LLO). Here, we performed quantitative mitochondrial proteomics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…Although mechanical force has been reported as an inducer of mitochondrial fission in animal cells, such fission is still dependent on Drp1 (Helle et al, 2017). However, it has also been reported that human cell infection by Listeria monocytogenes can trigger Drp1-independent fission of the mitochondrial network (Carvalho et al, 2020). Conidiation in A. nidulans might represent an interesting model to dissect DnmA -dependent and -independent mechanisms of mitochondrial fission.…”
Section: Mitochondrial Fission Is Connected To Development and Inducementioning
confidence: 99%
“…Although mechanical force has been reported as an inducer of mitochondrial fission in animal cells, such fission is still dependent on Drp1 (Helle et al, 2017). However, it has also been reported that human cell infection by Listeria monocytogenes can trigger Drp1-independent fission of the mitochondrial network (Carvalho et al, 2020). Conidiation in A. nidulans might represent an interesting model to dissect DnmA -dependent and -independent mechanisms of mitochondrial fission.…”
Section: Mitochondrial Fission Is Connected To Development and Inducementioning
confidence: 99%
“…L. monocytogenes elicits mitochondrial fragmentation via multiple mechanisms. The pore-forming toxin LLO causes loss of mitochondrial membrane potential and reduces ATP generation [115], increases expression of MIC10, a critical component of the mitochondrial contact site and cristae organizing system (MICOS) complex [116], and induces mitochondrial fission independent of the dynamin related protein 1 (DRP1) [117]. Altering dynamics of mitochondrial fusion during infection affects survival of Listeria, suggesting that it manipulates mitochondria dynamics to establish an infection [115].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Whilst the molecular mechanisms underlying the oligomerization of NLRX1 by LLO remain to be determined, LLO has been shown to trigger Ca 2+ influx into the host cytoplasm, 60,62 and from there into the mitochondria by the mitochondrial calcium uniporter (MCU) complex. Interestingly, MCU protein 1, a component of the MCU complex, was shown to be enriched following L. monocytogenes infection 63 . Although further study is warranted, it is possible that LLO‐mediated oligomerization of NLRX1 indirectly or directly drives mitochondrial matrix Ca 2+ overload, which can lead to mitochondrial dysfunction.…”
Section: Pathogen Sensingmentioning
confidence: 99%